Scutellarin Enhances Antitumor Effects and Attenuates the Toxicity of Bleomycin in H22 Ascites Tumor-Bearing Mice - Nie, Juan; Yang, Hong-Mei; Sun, Chao-Yue; Liu, Yan-Lu; Zhuo, Jian-Yi; Zhang, Zhen-Biao; Lai, Xiao-Ping; Su, Zi-Ren; Li, Yu-Cui (Frontiers in Pharmacology, 2018)
Bleomycin (BLM) is a broad spectrum anti-tumor drug and inducing pulmonary fibrosis. As an anti-tumor drug without immunosuppression, it is urgent to find a drug that reduces the side effects of BLM. Scutellarin (SCU), a flavone extracted from Erigeron breviscapus (Vant.) Hand-Mazz, has anti-inflammatory activity and ability to inhibit tumor cell growth, migration, and invasion. However, the combined role of SCU and BLM treatment in tumor is unclear. This study aimed to investigate the possible effect and related mechanisms of BLM combined with SCU in the treatment of tumor through in vivo and in vitro experiments. In vivo experiments showed that BLM combined with SCU in the treatment of mice bearing H22 ascites tumor prolonged the survival time, alleviated BLM-induced pulmonary fibrosis, reduced the production of TNF-α; IL-6, and the levels of MDA and MPO. BLM combined with SCU increased the apoptotic rate of H22 ascites cells and the levels of cleaved-caspases-3 and -8. Furthermore, BLM combined with SCU increased the protein expression of p53 and gene expression of miR-29b, and decreased the expression of TGF-β1. In vitro experiment results showed that BLM combined with SCU inhibited the viability of H22 cells and MRC-5 cells, promoted H22 cell apoptosis, up-regulated the protein expression of p53 and down-regulated the protein expression of α-SMA and collagen-I in MRC-5 cells. These experimental results suggested that SCU could enhance the anti-tumor effect of BLM and reduce BLM-induced pulmonary fibrosis, indicating SCU as a potential adjuvant for BLM in the future.